2011
DOI: 10.5897/ajb11.1227
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of two neuroendocrinecorrelated genes associated with body weight and reproductive traits in Jinghai yellow chicken

Abstract: In this study, insulin-like growth factor binding protein 2 (IGFBP-2) and signal transducers activators of transcription 5b (STAT5b) gene were studied as candidate gene associated with body weight and reproductive traits of the Jinghai Yellow chicken. Single nucleotide polymorphisms (SNPs) of the IGFBP-2 and STAT5b genes were examined in both Jinghai Yellow chicken and three reference chicken populations by PCR-SSCP. Two SNPs (T3746TG and CC3753TT) were detected in the IGFBP-2 gene. One SNP (C8066T) was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The effect of IGFBPII gene polymorphism in intron 2 on the growth rate of Kampung indigenous chickens was analyzed and three genotypes of CC, CT and TT were observed that the genotypic frequency of CT was higher than other genotypes and the allelic effect of C allele was greater than T allele and significant correlations were obtained with growth rate at 8-4 and 8-12 weeks of age (P<0.05) [23]. Investigation the polymorphism of IGFBPII gene in introns 1 and 3 with body weight and reproductive traits in four Chinese native chicken breeds revealed significant correlations between genotypes and body weight at the time of hatch and egg weight at day 300 in Jinghai Yellow breed [40]. In another study carried out by these researchers, intron 2 region of IGFBPII gene was studied in this population and three genotypes of AA, AB and BB (equivalent to CC, CT and TT in the Mazandaran native fowls population) were detected and no significant correlation was found between genotypes and body weight at 4, 8, 12 and 16 weeks of age.…”
Section: Discussionmentioning
confidence: 89%
“…The effect of IGFBPII gene polymorphism in intron 2 on the growth rate of Kampung indigenous chickens was analyzed and three genotypes of CC, CT and TT were observed that the genotypic frequency of CT was higher than other genotypes and the allelic effect of C allele was greater than T allele and significant correlations were obtained with growth rate at 8-4 and 8-12 weeks of age (P<0.05) [23]. Investigation the polymorphism of IGFBPII gene in introns 1 and 3 with body weight and reproductive traits in four Chinese native chicken breeds revealed significant correlations between genotypes and body weight at the time of hatch and egg weight at day 300 in Jinghai Yellow breed [40]. In another study carried out by these researchers, intron 2 region of IGFBPII gene was studied in this population and three genotypes of AA, AB and BB (equivalent to CC, CT and TT in the Mazandaran native fowls population) were detected and no significant correlation was found between genotypes and body weight at 4, 8, 12 and 16 weeks of age.…”
Section: Discussionmentioning
confidence: 89%